Exploring the Therapeutic Role of Physical Activity in Psychotic Disorders: Cognitive, Somatic, and Mental Health Impacts - Klaudia Fikas; Kamil Chwaliszewski; Dorota Waz; Michał Mazur; Jakub Szarłowicz; Zofia Goliszek; Karolina Łucja Sobek; Wiktoria Tabin-Barczak; Aldona Sokołowska; Sebastian Samuła (Quality in Sport)
Introduction and Purpose: